2012
DOI: 10.1186/ar4090
|View full text |Cite
|
Sign up to set email alerts
|

Murine Borrelia arthritis is highly dependent on ASC and caspase-1, but independent of NLRP3

Abstract: IntroductionThe protein platform called the NOD-like-receptor -family member (NLRP)-3 inflammasome needs to be activated to process intracellular caspase-1. Active caspase-1 is able to cleave pro-Interleukin (IL)-1β, resulting in bioactive IL-1β. IL-1β is a potent proinflammatory cytokine, and thought to play a key role in the pathogenesis of Lyme arthritis, a common manifestation of Borrelia burgdorferi infection. The precise pathways through which B. burgdorferi recognition leads to inflammasome activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
1
21
1
Order By: Relevance
“…Cells were pretreated with MnTBAP (100 mM) or CsA (0.5 mg/ml) for 30 min, followed by incubation with albumin (10 mg/ml) for 48 h. Recently, the NLRP3 inflammasome has received increasing attention because of its involvement in the development and progression of various diseases (21,22 (24) demonstrated that the downstream signaling components of the NLRP3 inflammasome, including caspase-1, IL-1␤, and IL-18, were significantly upregulated in the kidneys of proteinuric adults and were correlated with proteinuria severity. However, caspase-1, IL-1␤, and IL-18 expression can also be stimulated via NLPR3-independent pathways (23,25,26). In the present study, we observed that NLRP3 itself was up-regulated in the kidneys of proteinuric children and positively correlated with proteinuria severity.…”
Section: Discussionsupporting
confidence: 50%
“…Cells were pretreated with MnTBAP (100 mM) or CsA (0.5 mg/ml) for 30 min, followed by incubation with albumin (10 mg/ml) for 48 h. Recently, the NLRP3 inflammasome has received increasing attention because of its involvement in the development and progression of various diseases (21,22 (24) demonstrated that the downstream signaling components of the NLRP3 inflammasome, including caspase-1, IL-1␤, and IL-18, were significantly upregulated in the kidneys of proteinuric adults and were correlated with proteinuria severity. However, caspase-1, IL-1␤, and IL-18 expression can also be stimulated via NLPR3-independent pathways (23,25,26). In the present study, we observed that NLRP3 itself was up-regulated in the kidneys of proteinuric children and positively correlated with proteinuria severity.…”
Section: Discussionsupporting
confidence: 50%
“…Borrelia ‐exposed NOD1‐, NOD2‐, and RICK‐deficient murine cells still produced IL‐6 and TNF‐α. In contrast to previous in vitro data, NLRP3 did not seem to be involved in Lyme arthritis development in a murine model . ASC was pivotal in Lyme arthritis initiation as an important adapter protein in the inflammasome, involved in antigen presentation, lymphocyte migration, NF‐κB activation, and messenger RNA (mRNA) stability and via dedicator of cytokinesis 2 (Dock2) expression and Rac activation .…”
Section: The Role Of the Innate Immune System During The Early Stagescontrasting
confidence: 84%
“…Remarkably, B. burgdorferi infection of NOD2 deficiency C57BL/6 mice led to increased inflammation in joints and cardiac tissue when compared to wildtype mice, suggesting that NOD2 tolerization normally protects these mice against dissemination, possibly through the induction of multiple cytokines and interferons . A study by Oosting et al demonstrated that apoptosis‐associated speck‐like protein containing CARD (ASC)/caspase‐1 induction was crucial for IL‐1β production of in murine Lyme arthritis. The activation and secretion of IL‐1β occurred independently from NOD2/RICK, as well as NOD‐like receptor‐family member protein 3 (NLRP3) activation, while the TLR2‐MyD88 pathway was crucial for IL‐1β production.…”
Section: The Role Of the Innate Immune System During The Early Stagesmentioning
confidence: 99%
“…Interestingly, two caspase-1 substrates act together to achieve balanced control of Helicobacter infection and avoid excessive gastric pathology (57). The gram-negative spirochete, Borrelia burgdorferi , a pathogen of chronic Lyme disease-associated arthritis, activates the inflammasome in a manner dependent on ASC and caspase-1, but not NLRP3 (58, 59). In addition, IL-1 is a major pathogenic mediator of Lyme arthritis and is not required for control of Lyme borreliosis in murine models (59, 60).…”
Section: The Pathogenic Roles Of Nlrp3 Inflammasome Activation In Bacmentioning
confidence: 99%